THE NORTHERN AND ARCTIC SPECIFICS OF SOLVING THE PROBLEM OF FOOD SECURITY - Valentin A. Ivanov (Север и рынок: формирование экономического порядка, 2022)
The results of scientific research on the features and priority areas of strengthening food security of the population of the northern and Arctic territories are presented. The theoretical and methodological basis was the works of scientists in the field of food security. Analytical and statistical methods, methods of analogies, and expert assessments were used. The sources of information were data on the socio-economic development of the regions of the Far North and areas equated to them, Unified Interdepartmental Information and Statistical System (EMISS), Comistat, scientific publications on the research topic. The constituent elements of food security at the country and regional levels have been identified. Approaches to solving food security in the countries of the world are considered. The assessment of the state of food independence of Russia is given. The features, risks and threats to food security in extreme living conditions associated with the destruction of the material base of agriculture, the shortage of qualified personnel in the industry, the degradation and underdevelopment of rural infrastructure, the transport inadmissibility of remote areas for guaranteed food supply to their population, the decrease in food safety and quality, the inaccessibility of the poor to high-quality and safe food in accordance with rational consumption standards, the imperfection of regulatory and legal regulation and the organization of control over the quality and safety of food. The priority directions of ensuring food security are substantiated, including increasing own agricultural production, improving interregional links of food supplies to the regions of the North and the Arctic, improving the demographic situation, developing transport and trade infrastructures in rural areas, improving regulatory and legal regulation in the field of food safety and reducing rural poverty. The new approach to food security, which differs from the traditional one, is the sustainable development of rural areas, the creation ...